Electromagnetic interference shielding effectiveness of Cu powder/carbon black/epoxy resin composite film - Tam, Phuong Dinh; Thu, Vu Van (Vietnam Journal of Chemistry, 2015)
A novel composite of carbon black and Cu powder is mixed with epoxy resin in order to produce a composite material suitable for electromagnetic shielding applications. The microstructure of the composite material is investigated by mean of field emission scanning electron microscopy (FE-SEM) and Fourier transform infrared spectroscopy (FTIR). The electromagnetic interference shielding effectiveness (EMI-SE) of composite material is tested over frequency range of 8-12 GHz. According to the experimental results the maximum value of EMI-SE obtained at room temperature is approximately 4 dB and 7 dB for carbon black / epoxy resin sample and Cu powder / carbon black/epoxy resin sample with thinkness 500 µm, respectively. The influence of Cu powder mass and the thick film is also studied. The results indicate that the EMI-SE can reach approximately 25 dB at Cu powder 10 mass %.